Arsenic trioxide extends survival of Li–Fraumeni syndrome mimicking mouse - Jiabing Li; Shujun Xiao; Fangfang Shi; Huaxin Song; Jiaqi Wu; Derun Zheng; Xueqin Chen; Kai Tan; Min Lu (Cell Death and Disease, 2023)
Abstract Li-Fraumeni syndrome (LFS) is characterized by germline mutations occurring on one allele of genome guardian TP53. It is a severe cancer predisposition syndrome with a poor prognosis, partly due to the frequent development of subsequent primary tumors following DNA-damaging therapies. Here we explored, for the first time, the effectiveness of mutant p53 rescue compound in treating LFS-mimicking mice harboring a deleterious p53 mutation. Among the ten p53 hotspot mutations in IARC LFS cohorts, R282W is one of the mutations predicting the poorest survival prognosis and the earliest tumor onset. Among the six clinical-stage mutant p53 rescue compounds, arsenic trioxide (ATO) effectively restored transactivation activity to p53-R282W. We thus constructed a heterozygous Trp53 R279W (corresponding to human R282W) mouse model for the ATO treatment study. The p53 R279W/+ (W/+) mice exhibited tumor onset and overall survival well mimicking the ones of human LFS. Further, 35 mg/L ATO addition in drink water significantly extended the median survival of W/+ mice (from 460 to 596 days, hazard ratio = 0.4003, P = 0.0008). In the isolated tumors from ATO-treated W/+ mice, the representative p53 targets including Cdkn1a, Mdm2, and Tigar were significantly upregulated, accompanying with a decreased level of the proliferation marker Ki67 and increased level of apoptosis marker TUNEL. Together, the non-genotoxic treatment of p53 rescue compound ATO holds promise as an alternative for LFS therapeutic.